2018
DOI: 10.1186/s13028-018-0367-7
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and phylogenetic analysis of hepatitis E virus in pigs, wild boars, roe deer, red deer and moose in Lithuania

Abstract: BackgroundHepatitis E virus (HEV) is one of the major causes of acute viral hepatitis worldwide. In Europe, food-borne zoonotic transmission of HEV genotype 3 has been associated with domestic pigs and wild boar. Controversial data are available on the circulation of the virus in animals that are used for human consumption, and to date, no gold standard has yet been defined for the diagnosis of HEV-associated hepatitis. To investigate the current HEV infection status in Lithuanian pigs and wild ungulates, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 41 publications
4
33
0
Order By: Relevance
“…Additionally, in Europe, the seroprevalence of infections in wild boars ranged from 4.9% in Italy [ 28 ] to 57.4% in Spain [ 29 ]. A high percentage of infected wild boars was shown in Lithuania (25.9%) [ 30 ], Corsica (29.9%) [ 31 ], Slovenia (30%) [ 32 ], Belgium (34%) [ 33 ] and in the central part of Italy (56.2%) [ 34 ]. Regional differences in the occurrence of the frequency of HEV infections in wild boars in Poland were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in Europe, the seroprevalence of infections in wild boars ranged from 4.9% in Italy [ 28 ] to 57.4% in Spain [ 29 ]. A high percentage of infected wild boars was shown in Lithuania (25.9%) [ 30 ], Corsica (29.9%) [ 31 ], Slovenia (30%) [ 32 ], Belgium (34%) [ 33 ] and in the central part of Italy (56.2%) [ 34 ]. Regional differences in the occurrence of the frequency of HEV infections in wild boars in Poland were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in Europe revealed molecular evidence for HEV infection in wild boar and high HEV seroprevalences [24][25][26][27][28]. The HEV disease-dynamic in wild boar is similar to domestic pigs; the infection frequency also increases with age as well as the possibility of viral chronification [29].…”
Section: Introductionmentioning
confidence: 99%
“…In animals, zoonotic HEV is usually subclinical (Yugo and Meng 2013 ). Studies of HEV in cervids have mostly focused on European roe deer ( Capreolus capreolus ), red deer ( Cervus elaphus ), and sika deer ( Cervus nippon ) but fallow deer ( Dama dama ), white-tailed deer ( Odocoileus virginianus ), and European moose ( Alces alces ) have also been studied (Yu et al 2007 ; Zhang et al 2008 ; Reuter et al 2009 ; Boadella et al 2010 ; Forgách et al 2010 ; Rutjes et al 2010 ; Dong et al 2011 ; Medrano et al 2012 ; Lin et al 2014 , 2015 ; Larska et al 2015 ; Lhomme et al 2015 ; Serracca et al 2015 ; Kubankova et al 2015 ; Zhang et al 2015 ; Kukielka et al 2016 ; Neumann et al 2016 ; Roth et al 2016 ; Anheyer-Behmenburg et al 2017 ; Di Bartolo et al 2017 ; Thiry et al 2017 ; Weger et al 2017 ; Spancerniene et al 2018 ; Trojnar et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, only HEV-3 has been found in deer in Europe (Reuter et al 2009 ; Boadella et al 2010 ; Forgách et al 2010 ; Serracca et al 2015 ; Kubankova et al 2015 ; Kukielka et al 2016 ; Anheyer-Behmenburg et al 2017 ; Di Bartolo et al 2017 ; Thiry et al 2017 ; Spancerniene et al 2018 ). HEV seroprevalences have ranged 0.0–13.9% in Europe, and related HEV RNA prevalences have ranged 0.0–34.4% (Reuter et al 2009 ; Boadella et al 2010 ; Forgách et al 2010 ; Rutjes et al 2010 ; Larska et al 2015 ; Lhomme et al 2015 ; Serracca et al 2015 ; Kubankova et al 2015 ; Kukielka et al 2016 ; Neumann et al 2016 ; Roth et al 2016 ; Anheyer-Behmenburg et al 2017 ; Di Bartolo et al 2017 ; Thiry et al 2017 ; Spancerniene et al 2018 ; Trojnar et al 2020 ). HEV RNA prevalences over 10% have been reported in Hungary (Reuter et al 2009 ; Forgárch et al 2010 ), Lithuania (Spancerniene et al 2018 ), Italy (Di Bartolo et al 2017 ), and Spain (Boadella et al 2010 ; Kukielka et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%